Extensive gastric necrosis secondary to acute gastric dilatation: A case report. (February 2019) - Murakami, Chikako; Irie, Wataru; Sasaki, Chizuko; Nakamaru, Naomi; Sakamoto, Momoko; Nagato, Junpei; Satoh, Fumiko
Highlights: A man developed gastric necrosis secondary to acute gastric dilatation. He was seen at 3 different hospitals and discharged home. Early diagnosis and prompt treatment are required for treatment. Abstract: We report a case of sudden death in a patient who developed extensive gastric necrosis secondary to acute gastric dilatation. A 36-year-old man with mental retardation (but without difficulties in activities of daily living), developed an illness after a meal out with friends, necessitating 3 hospital visits. He returned home after receiving drug therapy; however, his condition deteriorated, and he was transferred to our hospital via ambulance. Whole-body computed tomography performed upon admission revealed gastric dilatation. A stomach tube was inserted, and 2000 mL of gastric aspirate was obtained. The patient died approximately 5 h later despite receiving treatment. Autopsy revealed 1000 mL of gastric contents and extensive gastric necrosis. He was diagnosed with extensive gastric necrosis secondary to acute gastric dilatation.